Visible-Light-Driven SO42-/TiO2 Photocatalyst Synthesized from Binh Dinh (Vietnam) Ilmenite Ore for Rhodamine B Degradation - Tan Lam Nguyen; Viet Dinh Quoc; Thi Lan Nguyen; Thi Thanh Thuy Le; Thanh Khan Dinh; Van Thang Nguyen; Phi Hung nguyen (My University, 2021)
Visible-Light-Driven SO42-/TiO2 Photocatalyst Synthesized from Binh Dinh (Vietnam) Ilmenite Ore for Rhodamine B Degradation
Keywords: SO42-/TiO2